Coco de roda novo quilombo: da roda ao centro, imagens e símbolos de uma tradição - Barreto, Janaina Lucene Mendonza (2017)
This research aims to identify and analyze, from a phenomenological approach as well as interviews, some visual elements of the Coco de Roda do Ipiranga New Quilombo, artistic and cultural manifestation that occurs in the municipality of Conde, Paraíba. The elements that we identify in the course of research and that will be approached are: the hype; The coconut wheel; The bow and the garments. It is important to consider that the Coco de Roda here studied and debated, in its visual elements, is a form of resistance and artistic and cultural expression of great relevance for the society of Paraiba and for the country, considering its tradition and musical richness, of dance , Of the visual elements, in short, of all living and latent culture. Thus, by emphasizing and discussing the visual elements, we intend to contribute, on the one hand, to the scientific knowledge and knowledge present in the University, particularly for the fields of visual arts, culture and anthropology and, on the other hand, to strengthen the idea And the conviction that it is a significant cultural manifestation for society and, for the moment, for cultural public policies at the local, regional and national levels.